Relationship between dyslipidemia and diabetic retinopathy: A systematic review and meta-analysis. Issue 36 (September 2018) - Zhou, Yue; Wang, Changyun; Shi, Ke; Yin, Xiaolong
Abstract: Background: The association between serum lipids and diabetic retinopathy (DR) was controversial. Therefore, we performed a meta-analysis to evaluate the relationship between triglycerides (TG), serum total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C), and DR. Methods: A systematic review and meta-analysis of observational studies was carried out to explore the association between serum lipids and DR. Studies related were initially indentified by searching PubMed, Cochrane Library, and Elsevier databases through June, 2017. Then a manual retrieval was also performed. RevMan 5.3 software was used to calculate the pooled mean differences (MDs) and related 95% confidence intervals (CIs). To test the stability of the final results, a sensitivity analysis was also performed. Results: A total of 7 studies were included in this meta-analysis. When compared with the controls, the DR cases did not show significantly higher TG levels (MD 9.18 mg/dL, 95%CI –4.14 to 22.49, P  = .18), higher TC levels (MD 3.77 mg/dL, 95%CI: –2.45 to 9.98, P  = .24), as well as lower HDL-C levels (MD –1.14 mg/dL, 95%CI: –2.43 to 0.15, P  = .08). But slightly higher LDL-C levels were observed (MD 3.74 mg/dL, 95%CI: 0.13–7.35, P  = .04). In addition, whether serum lipids involved in the progression of DR were relatively unexplored, but fenofibrate was confirmed to benefit the DR cases. Conclusions: Based on recent published data, we did not find obvious differences in TG, TC, and HDL-C levels between patients with DR and without DR. However, slightly higher LDL-C levels were observed in the DR cases.